Deindustrialization – Opportunity or Threat? - Rainer Przywara (Athens Journal of Business & Economics, 2017)
The term ‘deindustrialization’ stands for an element of structural change, indicating some form of decline within the secondary sector of a national economy. Sociologists use relative decline of manufacturing as their standard definition while economists often consider reductions in sectoral output as equally or even more important. There is a variety of other current descriptions. Rigid definitions were constituted and utilized in a model of industrialization and deindustrialization based on compound annual growth rates (CAGRs) of macro-economic indicators. For this article, the scenario model was applied on twelve mature countries (i.e. fully industrialized states beyond their maximum relative employment in manufacturing). The analysis covers the years 1973-2008 with successive 15 + 5 +15-year sub-periods. On the basis of the model-based findings and additional socio-economic analyses, different paths of industrial development (patterns of deindustrialization) were distinguished for mature economies with regard to their final outcome, i.e. the sectoral parameters and the resulting GDP per capita, employment rate and trade indicators.